Comparison of the ground-based and satellite total ozone measurements over the Antarctic stations - V. O. Kravchenko (Ukrainian Antarctic Journal, 2008)
Comparison of the ground-based and satellite total ozone content (TOC) measurements in the atmosphere over the Antarctic stations Akademik Vernadsky, Rothera, Halley and Amundsen-Scott has been carried out. Similar discrepancy analysis is made using global network of the ground-based ozonometric stations from the beginning of the regular satellite observations (1978). Slowing of the long-term global ozone losses has observed during last decade and recovering of the ozone layer is forecasted for the next decades. Therefore, the accuracy requirements to the ozone change registration are increased, that, in turn, requires corresponding analysis of the measurement errors. In this work, the EP-TOMS satellite data of 1996-2005 are used. Satellite daily TOC values are taken by the last 8th Version of the algorithm introduced in 2004 and empirically corrected in 2007. Influence of the seasonal TOC changes over Antarctic region on the difference between ground-based and satellite measurements is analyzed. The most persistent features are: 1) significant increase of the dispersion of the relative “satellite – station” difference in the period of the spring TOC decrease and ozone hole formation and 2) difference dependence on the TOC level.